2021
DOI: 10.1088/1742-6596/1747/1/012004
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-Converting Enzyme 2 (ACE2) of marine biota: a preliminary study of potential therapy for SARS-CoV-2 infection

Abstract: A new coronavirus, SARS-CoV-2, is responsible for the current pandemic causing severe respiratory disease. It has been known that the receptor for SARS-CoV-2 entry into the host cell is the angiotensin-converting enzyme 2 (ACE2). This receptor is expressed in a wide array of organs, for example, the kidneys and gastrointestinal tract, but rarely present in the circulation. The soluble form of ACE2 proposed as a potential therapy for SARS-CoV-2 infection. This research aimed to explore angiotensin-converting en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Previous studies look at the challenges faced by teachers during the pandemic in the different dimensions pertaining to specific subjects (Sugianto and Ulfah, 2020; Gurung, 2021; Hermansyah and Aridah, 2021; Barrow et al. , 2021; Borba, 2021; Ambawati et al. , 2021) in distinct geographical contexts like Israel, England, China, Portugal (Donitsa-Schmidt and Ramot, 2020; La Velle et al.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies look at the challenges faced by teachers during the pandemic in the different dimensions pertaining to specific subjects (Sugianto and Ulfah, 2020; Gurung, 2021; Hermansyah and Aridah, 2021; Barrow et al. , 2021; Borba, 2021; Ambawati et al. , 2021) in distinct geographical contexts like Israel, England, China, Portugal (Donitsa-Schmidt and Ramot, 2020; La Velle et al.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, ACE2 ( 234 ) of Delphinapterus leucas (Beluga whale) had a binding affinity of −988.5 kcal/mol towards the SARS-CoV-2 spike glycoprotein which is comparable to the hACE2 binding affinity (−946.4 kcal/mol) to the spike glycoprotein. Thus, ACE2 and ACE2-like structures from the marine biota could be used as decoys for viral binding [ 197 ]. Fayed et al [ 198 ] screened several marine compounds for their pharmacophore potentials against SARS-CoV-2 Mpro (6lu7 and 6y2f), spike glycoprotein, and RNA Polymerase, and reported that compounds with a flavonoid core, acyl indole, and pyrrole carboxamide alkaloids performed better.…”
Section: Potential In Silico and Pre-clinical Studies Of Marine-deriv...mentioning
confidence: 99%
“…Heptafuhalol A (190), a phlorotannin fuhalol from Sargassum spinuligerum also exhibited strong binding affinity towards Mpro (−14.60 kcal/mol) by interacting with some amino acid residues within the protease receptor including Thr24, Ser46, Asn142, Glu166, and Pro168. Furthermore, other fuhalol and phlorthol phlorotannin including phlorethopentafuhalol A (191) and B (192), pseudopentafuhalol C (193), hydroxypentafuhalol A (194), pentaphlorethol B (195), aeruginosin 98B (196), resinoside B (197), pentaphlorethol A (198), and tunichrome An2 (199) also have promising SARS-CoV-2 protease inhibitory potentials. Also, the flavonoids -apigenin-7-O-neohesperidoside (rhoifolin) (200), luteolin-7-rutinoside (201), and resinoside B (197) (from the brown alga Sargassum spinuligerum) bind to SARS-CoV-2 Mpro with great affinity (−12.4 kcal/mol) [134].…”
Section: In Silico Studies Of Other Secondary Metabolites (Phytochemi...mentioning
confidence: 99%
See 1 more Smart Citation